Ecosystem-based IPAS modules: traces of innovation by pre-service elementary school teachers in 21st-century learning - Jeane Kalengkongan; Deane Umboh (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study examines how pre-service elementary teachers develop pedagogical competence through a project-based learning experience involving the design of ecosystem-based IPAS (integrated science and social studies) modules. The study aims to explore (1) the instructional design process, (2) the characteristics and quality of the modules produced, and (3) participants' perceptions of their pedagogical competence development. A qualitative case study design was employed involving 30 pre-service teachers enrolled in a primary teacher education program. Data were collected through classroom observations, document analysis of instructional modules, and semi-structured interviews, and were analyzed thematically. Module quality was further examined using expert validation criteria. The findings indicate that pre-service teachers demonstrated emerging pedagogical competence, particularly in aligning content with learning objectives and adapting instructional materials to students' characteristics. The modules produced demonstrate satisfactory content and instructional quality, while technical components, such as organization and visual presentation, were less consistent. Interview data suggest that the project supported reflective engagement with teaching practices, although participants reported challenges in simplifying scientific concepts and using digital tools effectively. This study contributes to the literature by providing an empirical account of how project-based learning supports the development of pedagogical competence in integrated science instruction. It highlights the importance of combining authentic design tasks with structured pedagogical and technical support in teacher education programs.